The little pulutan book - Gonzalez, Gene R. (Mandaluyong City Anvil Publishing, Inc., 2015)
This cookbook offers an assortment of pulutan dishes that are guaranteed to go well with any kind of beer or liquor. There is something here for everyone, form crispy finger foods to fancy meat dishes. For those who love to cook as well as to drink, this little collection of exciting pulutan is sure to please.
1. Crispy dulong okoy -- 2. Adobong tokwa -- 3. Kangkong fritters -- 4. Banana-shrimp fritters -- 5. Barbecued isul -- 6. '60s fried spring chicken -- 7. Kinilaw na suaje -- 8. Quek-quek -- 9. Crispy biya or asohos -- 10. Kakaibang lumpiang shanghai -- 11. Ampaw Mayon express -- 12. Chicken pandan -- 13. Crispy chili caramel shrimp -- 14. Sizzling oysters -- 15. Ditak-ditak -- 16. Garlic chicken wings -- 17. Nonstop peanuts -- 18. Potato, smoked fish and egg croquettes -- 19. Gene's spring rolls -- 20. Ginataang mushrooms -- 21. Salpicado -- 22. Baked mussels with taba ng talangka -- 23. Sizzling bangus sisig -- 24. Lemon shrimp popcorn -- 25. Gene's pinsec frito -- 26. Anisadong hipon -- 27. Adobadong mushrooms -- 28. Baked peppers stuffed with longaniza and kesong puti -- 29. Cheese fritos -- 30. Baked clams with pinoy boursin -- 31. Shrimp toast -- 32. Gene's favorite frensh fries -- 33. Potato croquettes -- 34. Sizzling balut -- 35. Pritong kesong puti na may linga -- 36. Crusty soda cracker wings -- 37. Quekiam -- 38. Crispy itik -- 39. Nilasing na hipon -- 40. Bola-bolang panciteria -- 41. Chili-garlic squid and cucumber salad -- 42. Glossary.
Keywords: Food and beer pairing -- Philippines; Snack foods -- Philippines; Cooking, Philippine